Behavior of the gum from Enterolobium cyclocarpum in the preparation peach nectar - Delmonte, María Lucía; Rincón, Fernando; León de Pinto, Gladys; Guerrero, Rocío (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>Enterolobium cyclocarpum, (caro-caro), species widely disseminated in Venezuela, produces gum with high yield. It was studied the behavior of this hydrocolloid as additive in the preparation of peach nectar. It was carried out six treatments using different gum concentration (0.20; 0.30; 0.50; 0.70; 1%) wich were compared with a treatment without gum. There were measured physicochemical characteristics (acidity, pH, soluble solids, viscosity and stability) and sensorial attributes of the product. A random desing of blocks with six repetitions was applied. The results showed that the viscosity exhibited by the product obtained, using the highest gum concentration (1%) increased significatively (P<0.05) in comparison with the values shown by the produt obtained with the treatments using lower gum concentration (0.20; 0.30; 0.50; and 0.70%) and from the control treatment. In addition, it was also observed the lowest sedimentation value of the product obtained with the highest gum concentration. The panel prefered the peach nectar prepared using the highest gum concentration which exhibited a positive correlation with texture (r= 0.95) and flavor (r= 0.88). The results of this investigation support the functionality of E. cyclocarpum gum as additive in the preparation of peach nectar